Optimal Action of Soft Open Points in Distribution Systems Based on Single and Multiple Objective Particle Swarm Optimization: A Comparative Approach (Journal of University of Babylon for Engineering Sciences, 2024)
Distribution networks of electrical power are becoming increasingly active through integration of small generating units. However, the topology of the distribution network may hinder large scale integration of those generating units thereby decreasing the benefits of an active distribution network. Soft open points (SOPs) are considered one of the solutions to alleviate the hampering of integration of local sources by altering the topology of the distributed network. In this paper, the problem of finding the optimal operating points of  SOPs are analyzed and investigated. Two approaches are adopted; by using single objective particle swarm optimization  (PSO) and multiple objective (MOPSO). In the former, a set of objectives are optimized on a one by one bases whereas in the second method, the set of objectives are optimized together at the same time. The set of objectives are the typical, active power loss, voltage profile and feeder load balancing. A comparative approach is adopted in this paper with the intention of finding the best approach that yield optimum points. Optimum points which are defined as a set of active/reactive powers for each converter of the SOP. These optimum points are further employed by designers as reference settings for the control system which governs the local operation of the SOP system.Results from simulations carried out on the IEEE 33 bus system with and without multi capacity local energy sources, shows that the three objectives are better optimized using PSO than  MOPSO keeping in mind that the PSO requires less computation effort compared to MOPSO. Moreover, better PSO performance is observed as the amount of power injected by a distributed source (DG) increases. The former is also true when the system is optimized by MOPSO.